In Vivo Evaluation of Mechanically Processed Stromal Vascular Fraction in a Chamber Vascularized by an Arteriovenous Shunt - Bong-Sung Kim; Shih-Heng Chen; Mauro Vasella; Marco Guidi; Epameinondas Gousopoulos; Nicole Lindenblatt; Huang-Kai Kao (MDPI AG, 2022)
Mechanically processed stromal vascular fraction (mSVF) is a promising source for regenerative purposes. To study the in vivo fate of the mSVF, we herein used a vascularized tissue engineering chamber that insulates the target mSVF from the surrounding environment. In contrast to previous models, we propose an arteriovenous (AV) shunt between saphenous vessels in rats without a venous graft. Mechanical SVF was processed from the fat pads of male Sprague Dawley rats, mixed with a fibrin hydrogel and implanted into an inguinal tissue engineering chamber. An arteriovenous shunt was established between saphenous artery and vein. On the contralateral side, an mSVF-fibrin hydrogel mix without vascular axis served as a non-vascularized control. After two and six weeks, rats were sacrificed for further analysis. Mechanical SVF showed significant numbers of mesenchymal stromal cells. Vascularized mSVF explants gained weight over time. Perilipin and CD31 expression were significantly higher in the mSVF explants after six weeks while no difference in DAPI positive cells, collagen deposition and FABP4 expression was observed. Morphologically, no differentiated adipocytes but a dense cell-rich tissue with perilipin-positive cells was found after six weeks. The phosphorylation of ERK1/2 was significantly enhanced after six weeks while Akt activation remained unaltered. Finally, mSVF explants stably expressed and released VEGF, bFGF and TGFb. Vascularized mSVF is able to proliferate and express adipocyte-specific markers. The AV shunt model is a valuable refinement of currently existing AV loop models in the rat which contributes to the fundamental 3R principles of animal research.